Genotypes associated with tacrolimus pharmacokinetics impact clinical outcomes in lung transplant recipients. Issue 8 (4th July 2018) - Calabrese, Daniel R.; Florez, Rebecca; Dewey, Katherine; Hui, Christine; Torgerson, Dara; Chong, Tiffany; Faust, Hilary; Rajalingam, Raja; Hays, Steven R.; Golden, Jeffrey A.; Kukreja, Jasleen; Singer, Jonathan P.; et al.
Abstract: Most lung transplantation immunosuppression regimens include tacrolimus. Single nucleotide polymorphisms (SNPs) in genes important to tacrolimus bioavailability and clearance (ABCB1, CYP3A4, and CYP3A5) are associated with differences in tacrolimus pharmacokinetics. We hypothesized that polymorphisms in these genes would impact immunosuppression‐related outcomes. We categorized ABCB1, CYP3A4, and CYP3A5 SNPs for 321 lung allograft recipients. Genotype effects on time to therapeutic tacrolimus level, interactions with antifungal medications, concentration to dose (C0 /D), acute kidney injury, and rejection were assessed using linear models adjusted for subject characteristics and repeat measures. Compared with CYP3A poor metabolizers (PM), time to therapeutic tacrolimus trough was increased by 5.1 ± 1.6 days for CYP3A extensive metabolizers (EM, P < 0.001). In the post‐operative period, CYP3A intermediate metabolizers spent 1.2 ± 0.5 days less ( P = 0.01) and EM spent 2.1 ± 0.5 days less ( P < 0.001) in goal tacrolimus range than CYP3A PM. Azole antifungals interacted with CYP3A genotype in predicting C0 /D ( P < 0.001). Increased acute kidney injury rates were observed in subjects with high ABCB1 function (OR 3.0, 95% CI 1.1‐8.6, P = 0.01). Lower rates of acute cellular rejection were observed in subjects with low ABCB1 function (OR 0.36, 95% CI 0.07‐0.94, P = 0.02). Recipient genotyping may help inform tacrolimus dosing decisions and risk of adverse clinical outcomes.